И.ЮСУПОВ ЛИРИКАЛАРЫНДА ЗАТЛАСЫЎ АРҚАЛЫ ЖАСАЛҒАН МЕТАФОРАЛАР - Отепбергенова, Г. (SCIENCE and SOCIETY, 2024)
The article presents comments on metaphor as a special kind of artistic means. The views of foreign scientists on the theory of metaphor are taken into account. The types of metaphors are discussed, especially poetic metaphors.
Keywords: metaphor; poetic metaphor; linguistic metaphor; individual - author metaphor; individual style metaphor